La Capital: El Capital - Daher, Antonio (Revista EURE - Revista de Estudios Urbano Regionales, 1989)
US 160.000.000.000. One hundred and sixty billion dollars. Eight times the GNP. Ten times the national external debt. If Santiago is worth that much, if an appraisal exercise of the capital city leads to that conclusion, then the capital city is itself the main capital resource. This resource being the most scarce one in less developed countries, shares the space with another one that is relatively abundant: labor force. This article does not embody an apology of a centralist administration. But it does emphasize that Santiago represents a forty percent of GNP -percentage which is higher than that of any other economic sector- and by far the largest national Í€œenterpriseÍ€. Chile may count on Santiago as being the main installed capacity, the most strategic economic resource, and the more complex and important administration challenge. The question is what to do with Santiago. Does it need a mayor or a city manager? Í